(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Antimicrobial Peptides (AMPs) were first known as a group of innate immune products that mainly targets on the invading pathogens among multiple species. The essential mechanisms of action of AMPs toward microbial cells have been reported as electrostatic attraction and hydrophobic interaction between AMPs (cationic AMPs) and microbial cell membranes. These effects also contribute to the potential mechanism of anticancer activities of AMPs as well. The membrane difference between cancer cells and normal cells are believed to play significant roles in AMPs orienting process. Membrane selective targeting properties make AMPs promising candidates for alternative approach to solve the problems from anticancer drug resistance.